Government matters : welfare reform in Wisconsin - Mead, Lawrence M. (Princeton University Press, 2004)
""Good government" is commonly seen either as a formidable challenge, a distant dream, or an oxymoron, and yet it is the reason why Wisconsin led America toward welfare reform. In this book, Lawrence Mead shows in depth what the Badger State did and - just as important - how it was done. Wisconsin's welfare reform was the most radical in the country, and it began far earlier than that in most other states